Studi simulasi pada unit reformer primer di PT Pupuk Sriwidjaya Palembang - Sigit Abdurrakhman; Sutijan Sutijan; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2012)
Ammonia plant is the main part of fertilizer industry. Primary reformer is an unit operation where catalytic reaction between steam and methane take place, or it is known as steam methane reforming. The main raw material is steam (H2O) and natural gas with major content of methane (CH4). The objective of this research was to develop primary reformer unit process model to calculate temperature, pressure and composition profiles for steady state operation according to operating condition on Ammonia III plant in PT Pupuk Sriwidjaya Palembang.The assumption used was plug flow model both on the furnace side and on the catalytic reactor side for steady state conditions. The ordinary differential equations were solved using Runge Kutta method with Scilab software to get the conversion, pressure and temperature profiles on primary reformer. Variabels evaluated were temperature, pressure, and composition.The simulation result showed that an average error of 3.94 % compared to the operational plant data. For various operating conditions this simulation showed an average error of 7.01 %.